2008
DOI: 10.1021/la801080f
|View full text |Cite
|
Sign up to set email alerts
|

Lipid Bilayer Membrane with Atomic Step Structure: Supported Bilayer on a Step-and-Terrace TiO2(100) Surface

Abstract: The formation of a supported planar lipid bilayer (SPLB) and its morphology on step-and-terrace rutile TiO 2(100) surfaces were investigated by fluorescence microscopy and atomic force microscopy. The TiO 2(100) surfaces consisting of atomic steps and flat terraces were formed on a rutile TiO 2 single-crystal wafer by a wet treatment and annealing under a flow of oxygen. An intact vesicular layer formed on the TiO 2(100) surface when the surface was incubated in a sonicated vesicle suspension under the conditi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
134
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 79 publications
(143 citation statements)
references
References 103 publications
7
134
0
Order By: Relevance
“…23,24 On the other hand, with a high liposome concentration and a long incubation time, Tero et al claimed that PC liposomes can form similar bilayers on TiO2 (100) as that on SiO2 based on van der Waals interaction, and the attraction potential is 20-fold larger on TiO2. 25 Others reported that low pH, or incorporation of anionic lipids plus Ca 2+ is needed to form SLBs on TiO2. [26][27][28] The above studies mainly employed bulk planar TiO2 surfaces, and the overall impression is that it is more difficult to form PC SLBs on TiO2.…”
Section: Metal Oxidesmentioning
confidence: 99%
“…23,24 On the other hand, with a high liposome concentration and a long incubation time, Tero et al claimed that PC liposomes can form similar bilayers on TiO2 (100) as that on SiO2 based on van der Waals interaction, and the attraction potential is 20-fold larger on TiO2. 25 Others reported that low pH, or incorporation of anionic lipids plus Ca 2+ is needed to form SLBs on TiO2. [26][27][28] The above studies mainly employed bulk planar TiO2 surfaces, and the overall impression is that it is more difficult to form PC SLBs on TiO2.…”
Section: Metal Oxidesmentioning
confidence: 99%
“…25 A number of previous studies investigated the interaction between liposomes and TiO2 surfaces, where both liposome fusion and simple adsorption were reported depending on the lipid composition. [26][27][28][29][30][31][32][33][34][35] It needs to be noted that fusion takes place with negatively charged phosphatidylserine (PS) lipids in the presence of Ca 2+ , while liposomes composed solely of zwitterionic phospholipids only undergo adsorption in physiological conditions. Some work reported planar zwitterionic bilayers on TiO2 under acidic conditions.…”
Section: Introductionmentioning
confidence: 99%
“…In case of an adhesive vesicular layer, the photobleached region remains and no recovery proceeds because the vesicles were immobile and isolated from each other. 18,26,27 The bright spots in Figs. 4 and 5 were adsorbed vesicles, but we could not judge whether they adsorb on the SLB or on the substrate from the fluorescence images.…”
Section: Supported Lipid Bilayer On the Pvc Membranementioning
confidence: 99%
“…A thermally oxidized SiO 2 /Si substrate was also used as a control, because it is a standard sample in our previous studies, [18][19][20][21] where the preparation of vesicle suspensions and SLBs are described in more detail.…”
Section: Preparation Of Supported Lipid Bilayers By the Vesicle Fusiomentioning
confidence: 99%
See 1 more Smart Citation